Roads and Rural Development in Sub-Saharan Africa - Berg, Claudia N.; Blankespoor, Brian; Selod, Harris (Taylor and Francis, 2018)
This paper assesses the relationship between access to markets and land cultivation in sub-Saharan Africa. Using a geo-referenced panel over four decades (1970–2010) during which the road network was significantly improved, we find a modest impact of improved market accessibility on local cropland expansion – especially in places that are exposed to better agricultural production conditions – as well as suggestive evidence of an increase in the local intensity of cultivation. Suggestive evidence of a positive association between improved market accessibility and local GDP growth beyond the impact of cropland expansion could reflect the stimulation of non-agricultural activities.